The Effectiveness of Virtual Reality in Enhancing English Speaking Skills in English as a Foreign Language Classes - Wulandari, Fitri; Suyono, Akhmad; Kumalasari, Cyintia; Suryanti, Nunuk; Fajri, Rahmad Al (Journal of English Language and Education, 2026)
Speaking proficiency remains a persistent challenge in Indonesian EFL higher education, where students often demonstrate adequate linguistic knowledge but limited confidence and high speaking anxiety in oral communication. Although Virtual Reality (VR) has been widely discussed as an innovative tool in language learning, empirical evidence examining its effectiveness in improving both speaking performance and affective factors in Indonesian university contexts remains limited. The research employed a quasi-experimental design with pre-test and post-test measures to examine the effectiveness of Virtual Reality (VR) technology in improving speaking skills among second-ssemester EFL students at the Islamic University of Riau. The study involved administering assessments before and after the intervention, without a separate control group, allowing measurement of changes attributable to VR-assisted instruction. The findings indicate that the use of VR contributed to positive developments in students’ speaking abilities and learning motivation. Quantitative data showed improvements in several key areas, while qualitative feedback highlighted increased motivation and engagement. The research outputs include empirical evidence supporting the integration of VR in EFL speaking classes, comparative assessment data, and the development of an instructional model for VR-based activities. These results are aligned with recent studies and the original research objectives.